2016
DOI: 10.2527/jas.2015-9862
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extended postmortem aging and steak location on myofibrillar protein degradation and Warner-Bratzler shear force of beef M. semitendinosus steaks1

Abstract: The objective of this study was to evaluate the effect of steak location and postmortem aging on cooked meat tenderness and myofibrillar protein degradation of steaks from M. semitendinosus (ST). Following harvest and a 6 d chill period, the left ST was removed from carcasses of crossbred feedlot steers ( = 60, average hot carcass weight 427 ± 24 kg). Each ST was fabricated into ten 2.54-cm thick steaks originating from the proximal to distal end of the muscle. Steaks cut adjacent to each other were paired, va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 56 publications
1
19
0
1
Order By: Relevance
“…However, to our knowledge this is the first single interspecies comparative study in this manner. Loss of native bands or appearance of degradation products occur due to autolysis [ 32 , 33 ], which is a combination of tissue-specific metabolic processes that occur in many different species and are thus eventually comparable.…”
Section: Discussionmentioning
confidence: 99%
“…However, to our knowledge this is the first single interspecies comparative study in this manner. Loss of native bands or appearance of degradation products occur due to autolysis [ 32 , 33 ], which is a combination of tissue-specific metabolic processes that occur in many different species and are thus eventually comparable.…”
Section: Discussionmentioning
confidence: 99%
“…longissimus dorsi (Polati et al ., ) or M . semitendinosus (Phelps et al ., ). Moreover, numerous studies have shown that extending the time of the ageing process could improve the tenderness of beef (Colle et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…In beef, Phelps et al (2016) showed WBSF was impacted by location within the ST. Muscle was measured from proximal to distal with a decrease in WBSF when moving toward to the middle of the ST but increased again moving toward the distal end.…”
Section: Postmortem Protein Degradationmentioning
confidence: 99%